The Evolution of Views on the Rationale for Uses of Force Prior to the Establishment of Modern Institutions - Stanislav Valentinovich Korostelev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article addresses the issue of justification of uses of force in historical perspective. Formation of the modern doctrine of Just War originated in ancient Greece and Rome. Ancient postulates of rationale for just uses of force were initially rejected by early Christians, but then were developed in the writings of St. Augustine and Thomas Aquinas. Later religious doctrine of just war was developed and replaced by a secular one in the works of scientists, theologians, philosophers and lawyers, such as John Locke, Hugo Grotius, Jean Bodin, Thomas Hobbes, Emeric de Vattel. By the beginning of the century it became evident that self-survival regime, grounded in the doctrine of sovereignty, does not ensure the security of States, and this in turn led them to the creation of international institutions in the sphere of security. These institutions allow States to combine their resources to secure common interests.